EVALUATION OF DRILLING INDUCED DELAMINATION OF CARBON FIBER REINFORCED POLYMER COMPOSITE USING SOLID CARBIDE DRILLS - , Nagaraja; Mervin A. Herbert; Divakara Shetty; Vijay G S; Raviraj Shetty (European Scientific Journal, ESJ, 2014)
Delamination in drilling is an inter-ply failure phenomenon and has been recognized as the most common defect in drilling of carbon fiber reinforced polymer composites. This problem can affect not only the load carrying capacity of the produced-parts but also the reliability. In the present work, an attempt has been made to study the influence of process parameters (spindle speed, drill diameter, feed rate and point angle) on delamination in drilling of bi-directional carbon fabric reinforced polymer (BD CFRP) composite using uncoated and TiN coated solid carbide drills. Taguchi design of experiments (DOE), response surface methodology (RSM) and analysis of variance (ANOVA) techniques are employed for investigating the effects of process parameters on delamination. The results indicate that drill diameter has a significant influence on delamination, followed by spindle speed and feed rate. It is evident from the study that the experimental results of delamination factor are in good approximation with the predicted results as per RSM. The study reveals that the TiN coated solid carbide drills are preferred to uncoated solid carbide drills in reducing the drilling induced delamination. Furthermore, the study also reveals that the optimum parametric conditions required for minimum delamination in drilling of BD CFRP composite are drill diameter of 4 mm, feed rate of 10 mm/min, spindle speed of 1800 rpm and point angle of 90°.